Does Educational Tracking Affect Performance and Inequality? Differences-in-Differences Evidence across Countries - Eric A. Hanushek; Ludger Wößmann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2005)
Even though some countries track students into differing-ability schools by age 10, others keep their entire secondary-school system comprehensive. To estimate the effects of such institutional differences in the face of country heterogeneity, we employ an international differences-in-differences approach. We identify tracking effects by comparing differences in outcome between primary and secondary school across tracked and non-tracked systems. Six international student assessments provide eight pairs of achievement contrasts for between 18 and 26 cross-country comparisons. The results suggest that early tracking increases educational inequality. While less clear, there is also a tendency for early tracking to reduce mean performance. Therefore, there does not appear to be any equity-efficiency trade-off.
Keywords: I20; 330; Tracking; streaming; ability grouping; selectivity; comprehensive school system; educational performance; inequality; international student achievement test; TIMSS; PISA; PIRLS